13th Commonwealth International Sport Conference in Melbourne (13th Commonwealth International Sport Conference in Melbourne, 2006)
The 13th Commonwealth International Sport Conference at Moonee Valley Racing Club attracted 650 delegates from 41 countries. The international delegates comprised 40 percent of the total number.